EFEK MODERASI GENDER DAN USIA PADA PENGARUH LITERASI KEUANGAN TERHADAP PENGELOLAAN KEUANGAN PRIBADI PEGAWAI DI UNIVERSITAS MUHAMMADIYAH SUMATERA BARAT - Kevry Ramdany; Anne Putri (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2022)
This study aims to empirically examine the effect of financial literacy on employees' personal financial management. In addition, to empirically examine the moderating effect of gender and age on the effect of financial literacy on employees' personal financial management. To answer this goal, each variable will be processed using WarpPLS (Partial Least Square) software version 6.0. The results showed that financial literacy had a positive effect on personal financial management behavior, gender of men moderated the effect of financial literacy on personal financial management more than gender of women and older age groups moderated the effect of financial literacy on personal financial management than young people. Good financial literacy is one of the important factors in making a person's personal financial management decisions. The better financial literacy a person has, the better decision making in managing his personal finances will be.